Optimizing Student Literacy Through "Aksi" Applications - Wahyuningsih, Wahyuningsih; Arifah, Mir'atun Nur (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
This research aims to analyze the use of this application in improving students' numeracy literacy skills. Using a descriptive qualitative approach, data was collected and analyzed based on interviews with students, teachers and school principals at SD Negeri Ngringin. Observation of the learning process and documentation of other data are used to obtain valid research results. The results of this research show that the use of the AKSI application has an influence in improving students' literacy skills, especially on literacy goals and objectives. In terms of literacy targets, the AKSI application is able to increase the intensity of the use and application of numeracy in learning, increase the amount of non-mathematics learning that involves elements of numeracy literacy, increase online sites related to numeracy literacy, increase the number of numeracy literacy activities in schools, increase the frequency of borrowing numeracy literacy reading materials , and encourage the creation of school policies related to increasing numeracy literacy. Meanwhile, for literacy purposes, this application has an effect on increasing a person's knowledge through reading activities, increasing understanding in drawing conclusions from the information read, and growing and developing students' character.